Mass Voilence, Self-Censorship, and the Diasporic Web: When the Field Investigation Confronts Us With the Question of Online Positioning - Maillet, Léo (Swiss Journal of Sociocultural Anthropology, 2025)
Conducting research among populations affected by mass violence, especially when such violence takes place in colonial contexts, raises ethical and methodological challenges that require reflexivity. Drawing on fieldwork conducted among the Uyghur diaspora of Istanbul between 2021 and 2023 for my PhD on Uyghur bread-making, I propose to address these challenges by examining the question of representation. In this article, I show how the people I met in the field confronted me not only with the issue of the representations, as a researcher, produce, but also with my own online positioning regarding the mass violence they are facing in their homeland.